2019
DOI: 10.3390/app9163275
|View full text |Cite
|
Sign up to set email alerts
|

Flame Retardancy of Carbon Nanotubes Reinforced Carbon Fiber/Epoxy Resin Composites

Abstract: In order to study the effect of carbon nanotubes (CNTs) on the flame retardancy of carbon fiber (CF)/epoxy resin (EP) composites, CF/EP and CNTs/CF/EP composites were prepared by solution blending. The flame retardancy and thermal stability were studied by cone calorimetry and thermogravimetric analysis. It was found that CNTs and CF had a certain synergistic effect on improving flame retardancy and thermal stability of EP. The peak heat release rate of F7N7, which represents the EP composites with 0.7 wt % CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The decomposition product of APP chemically reacts with BN to promote the expansion of the residues. The maximum peak and valley of the DTG curves in Figure 9 demonstrate that the weight loss is the highest, consistent with the findings of Guo et al 40 …”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The decomposition product of APP chemically reacts with BN to promote the expansion of the residues. The maximum peak and valley of the DTG curves in Figure 9 demonstrate that the weight loss is the highest, consistent with the findings of Guo et al 40 …”
Section: Resultssupporting
confidence: 90%
“…The decomposition product of APP chemically reacts with BN to promote the expansion of the residues. The maximum peak and valley of the DTG curves in Figure 9 demonstrate that the weight loss is the highest, consistent with the findings of Guo et al 40 The pyrolysis activation energy of the three coatings is consistent with Table 4. The pyrolysis activation energies E α of 300-380 C increase from 46.64 kJ mol À1 (N0) to 57.56 kJ mol À1 (N3), representing a 23.4% increase.…”
Section: Pyrolysis Kinetic Analysissupporting
confidence: 89%
See 1 more Smart Citation
“…G.Q. Zhu [123] et al synthesized a series of CNTs/CF/EP composites and investigated the effect of CNTs on the flame retardancy and mechanical properties of CF/EP composites. The results showed that the addition of CNTs could improve the flame retardancy and smoke suppression of CF/EP composites.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Carbon fiber epoxy resin composites (CFE composites) have been widely used in many fields [16][17][18][19][20]. Because of their low density, low thermal expansion, high strength and fatigue characteristics, their performance in many aspects is superior to that of traditional metal materials [2,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%